posted by Trig .
(1/cos)^2 times (1/tan)-(1/tan)=tan
(1/cos^2) times (-2/tan)=tan
sq. root of (-2/cos^2)= sq. root of (tan^2)
sq. root of (2i)/cos=tan
I'm not sure if I did this right. If I didn't, can you show me the correct steps?
Thanks, I appreciate it.
sec^2(x)cot(x) - cot(x) = tan(x)
Convert everything to sine and cosine using the identity tan(x) = sin(x)/cos(x).
cos^-2(x)(cos(x)/sin(x)) - cos(x)/sin(x) = sin(x)/cos(x)
1/( cos(x)sin(x) ) - cos(x)/sin(x) = sin(x)/cos(x)
Note: it is important to write sin(x) as opposed to sin, because you may find equations that include different parameters -- sin(x) and sin(2x), for example.